Cloning and Expression of the Dengue virus Non-structural Protein 1 (NS1) in E. coli - Truong, Quoc Phong; Chu, Thi Minh Hai; Le, Van Hoang; Dang, Thi Huyen Trang (Old Journal, 2018)
Dengue is an infectious disease that poses a threat to approximately 3.9 billion people in 128 countries in the world. A report in 2013 indicates average of 390 million dengue infections per year. Non-structural protein 1 (NS1) is a highly conversed dengue virus glycoprotein and considered as a specific biomarker for serodiagnosis of dengue infection. In the present study, the ns1 gene encoding the non-structural protein 1 (NS1) from the Vietnam Dengue virus isolate was cloned and sequenced. The isolated ns1 gene was high identity with Dengue virus 1 polyprotein-like gene (gene ID: JQ045627.1). The ns1 gene was successfully inserted into the expression vector pET22b(+) in an open reading frame. The successful expression of recombinant NS1 protein (rNS1) in E. coli BL21 (DE3) was checked by SDS-PAGE and confirmed by Western blot. Some suitable conditions for high expression of rNS1 protein were 0.3 mM IPTG, 4 hours induction and initial inoculum density of 0.2.